Use of open source mathematics textbooks in university courses (2019)
In the Undergraduate Teaching and Learning in Mathematics with Open Software and Text- books project we study the use of open source textbooks in the teaching and learning of mathematics at the university level (Beezer et al., 2018). The project gathers (a) real-time, individualized viewing data from three dynamic university textbooks for calculus, linear algebra, and abstract algebra; (b) ongoing surveys of users¿ descriptions of the textbook use; (c) users¿ questionnaires (beliefs and attitudes towards mathematics, technology, teaching, and learning); and (d) student performance (tests of knowledge and grades). The textbooks have been enhanced with a variety of features (WeBWorK, Geogebra, Interactive Reading Questions, and computational cells). In this article I highlight the theoretical and methodological approaches used in the project to answer two questions: How do students and instructors use textbooks? and How can we develop textbooks that will improve teaching and learning?